Transgenic plants regenerated from hairy roots of Nicotiana benthamiana: a promising host for transient expression of foreign proteins - Sindarovska, Y.R.; Gerasymenko, I.M.; Sheludko, Y.V.; Komarnytskyy, I.K.; Bannikova, M.A.; Kuchuk, N.V. (Цитология и генетика, 2005)
Hairy root cultures of Nicotiana benthamiana have been obtained by co-cultivation of leaf explants with Agrobacterium rhizogenes strain A4 harboring a binary vector plasmid, and transgenic nature of the obtained cultures was confirmed by PCR analysis. Transgenic plants were regenerated from hairy roots. The biomass yield of transgenic plants grown in vitro was almost two-fold higher than those of wild-type N. benthamiana plants. They differed from untransformed plants by short internodes, reinforced stem, thick and wrinkled leaves and more developed root system. The level of Agrobacterium-mediated transient expression of green fluorescent protein (GFP) in the regenerated plants was similar to that of untransformed plants.